2015
DOI: 10.1590/1415-52732015000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with central obesity in schoolchildren in Santa Catarina, Brazil

Abstract: A B S T R A C T ObjectiveThe aims of this article are to estimate the prevalence and to identify the sociodemographic factors and food consumption associated with central obesity in schoolchildren 6-10 years old of the State of Santa Catarina, Brazil. MethodsIt consists in a cross-sectional population-based study involving 4,963 schoolchildren enrolled in the public and private sectors. The dependent variable is central obesity investigated by measuring waist circumference and classified according to percentil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…While growing evidence has emphasised the role of physical inactivity in the development of obesity among children and adolescents [17,39,40,42], the present study did not find any significant association between total physical activity and general or abdominal obesity. The results of the study are consistent with those of other studies [17,28,44,46,49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While growing evidence has emphasised the role of physical inactivity in the development of obesity among children and adolescents [17,39,40,42], the present study did not find any significant association between total physical activity and general or abdominal obesity. The results of the study are consistent with those of other studies [17,28,44,46,49].…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of abdominal obesity, indicated by elevated WHtR, was higher than that reported in Lebanon (20.9%) [45], Saudi Arabia (33.1%) [46] and Portugal (22.5%) [40], but lower than that in Jordan (49.4%) [47]. Rates of elevated WC (48.8%) were higher than those found in Malaysia (11.3%) [48], Lebanon (14.1%) [45] and Brazil (5%) [49]. We noted a statistically significant difference between genders in the prevalence of general and abdominal obesity, with the risk of obesity being higher in males than in females.…”
Section: Discussionmentioning
confidence: 98%
“…3 In addition, in 2007 and 2008, the prevalence of abdominal obesity among 6 to 10-year-old schoolchildren in the state of Santa Catarina was observed to be 4.9%. 4 Studies have shown that the availability of places for physical activity and active leisure (PAAL) close to home makes it more likely that these facilities will be used more often, because of ease of access. 5 Children and adolescents who report living close to such places tend to have lower body mass index (BMI) and lower values for other measurements of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The food groups of the PDFQ were classified as protective foods (vegetables and greens, vegetable soup, fruits, and natural juices) and risk foods (chocolate milk, sweets and desserts, chips, fast-food meals, industrialized snacks, artificial fruit juices, and soft drinks). 5 , 15 The consumption of protective foods was considered adequate when consumed more frequently or equal to six times a day; and inadequate when the listed foods were consumed less than five times a day. Conversely, the consumption of risk foods was classified as inadequate when its intake occurred more than three times a day; and as adequate when it occurred twice a day or less.…”
Section: Methodsmentioning
confidence: 99%
“…3 Therefore, the combined use of these three anthropometric indices (BMI, WC, and WtHR) allows more reliable estimates of the evaluation of abdominal obesity and, consequently, of the risk of developing CVD among children. 1 Differences between the prevalence of overweight among students in public and private schools is well-studied; 4,5 however, studies that assess the nutritional status of schoolchildren in the same school system, differentiating them by the geographic location of schools in the urban area of the same city, are still scarce. 6 There are also few studies that analyzed factors associated with the development of abdominal obesity among children, considering that most research focuses on investigating only the presence of general obesity.…”
Section: Introductionmentioning
confidence: 99%